2013
DOI: 10.1007/s10802-013-9773-5
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial Testing the Effectiveness of a Depression Prevention Program (‘Op Volle Kracht’) Among Adolescent Girls with Elevated Depressive Symptoms

Abstract: Depression rates rise dramatically from the early to late adolescence. Especially young adolescent girls with elevated depressive symptoms are at high risk for developing a depression during adolescence or adulthood. Therefore, the prevention of depression is important especially in this high-risk group. The aim of the present study was to examine the effectiveness of the Cognitive Behavioral Therapy (CBT) component of the depression prevention program 'Op Volle Kracht' (OVK) among Dutch adolescent girls with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 33 publications
5
46
3
4
Order By: Relevance
“…Consistent with the previous analyses, OVK was not effective at universal level [24] and selective level [25]. However, OVK was effective at an indicated level among adolescents girls [26] when it included only the first eight lessons based solely on CBT techniques. This is in line with Stice et al [21] who showed, that longer prevention programs lead to less positive outcomes.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…Consistent with the previous analyses, OVK was not effective at universal level [24] and selective level [25]. However, OVK was effective at an indicated level among adolescents girls [26] when it included only the first eight lessons based solely on CBT techniques. This is in line with Stice et al [21] who showed, that longer prevention programs lead to less positive outcomes.…”
Section: Introductionsupporting
confidence: 78%
“…Potential loss of power due to data clustering has to be considered, since the intervention will be conducted in small groups, with the mean of seven children in each group. Therefore, the ICC (estimated at 0.07 based on the results of Wijnhoven et al [26]) needs to be incorporated into the sample size calculation. The Variance Inflation Factor (VIF; [44]) equals 1.49, indicating that the sample size must be increased to 117.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The program has been implemented with universal (e.g., Pattison & Lynd-Stevenson, 2001), selective (e.g., Cardemil, Reivich, & Seligman, 2002), and indicated (e.g., Wijnhoven, Creemers, Vermulst, Scholte, & Engels, 2014) samples. Although typically a school-based intervention, PRP also has been delivered in primary care clinics (Gillham, Hamilton, Freres, Patton, & Gallop, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…These results cannot be attributed to selection bias or other treatment effects, as children who were in active treatment were excluded from participation and a strict randomization process was followed. The influence of the participants’ knowledge of their allocation to the experimental or the control group between the screening and pre-assessment, a so-called expectancy effect (Arrindell 2001; Wijnhoven et al 2013), can also be ruled out because the participants were unaware of their allocation until after pre-assessment. A “test-retest effect,” wherein a change in mean scores towards less psychopathology between two measurements are observed without any formal intervention having yet taken place, could explain a decline in outcome measures between the two measurements.…”
Section: Discussionmentioning
confidence: 99%